2010
DOI: 10.1080/10572252.2010.481536
|View full text |Cite
|
Sign up to set email alerts
|

Getting an Invitation to the English Table—and Whether or Not to Accept It

Abstract: In this article, we trace the journey our professional writing program took from marginal area to well-supported specialty in an English department-a journey we made without sacrificing our commitment to prepare students for professional-level employment. In so doing, we explore the grounds of intellectual compatibility between our field and English studies and describe the conditions most conducive to professional writing's finding a respected place in English departments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…TPC has long been concerned with the departmental location of programs (Davis, 2001, p. 19; Rentz, Debs, & Meloncon, 2010; c.f., Yeats & Thompson, 2010) and being able to see whether departmental home has an effect on contingency is an important point for further research. For example, future research should consider do those contingent faculty working in departments outside of English have higher salaries?…”
Section: Resultsmentioning
confidence: 99%
“…TPC has long been concerned with the departmental location of programs (Davis, 2001, p. 19; Rentz, Debs, & Meloncon, 2010; c.f., Yeats & Thompson, 2010) and being able to see whether departmental home has an effect on contingency is an important point for further research. For example, future research should consider do those contingent faculty working in departments outside of English have higher salaries?…”
Section: Resultsmentioning
confidence: 99%
“…However, in a follow-up, Porter concedes that English is no longer a suitable home for professional communication. Rentz, Debs, and Meloncon similarly argue that there are still ways in which professional writing programs can thrive in English departments, and professional writing faculty should work to more explicitly define their value in English departments [23]. Regardless of where one falls in the departmental home debate, previous research has clearly shown that departments play an integral role in building a program's identity.…”
Section: Departmental Home and Research Identitymentioning
confidence: 94%
“…To successfully operate within these contexts, Charney's call for simpler, small-scale studies may be a way to manage the time restraints many face within departments that don't necessarily value larger-scale studies [36]. Additionally, Rentz et al call for technical communication scholars in English departments to better articulate the value of their work in order to shape perceptions of that work with colleagues [23]. One way technical communicators can more effectively articulate the impact of their work is to provide empirical evidence that defends their methodological choices and publication venue choices.…”
Section: Conclusion Limitations and Suggestions For Future Researchmentioning
confidence: 96%
See 1 more Smart Citation
“…graduate students, adjuncts and full-time non-tenure track) [5]. The prevalence of full-time tenure-track PTC faculty is growing [12], but these instructors are still often the "lone rangers" of their specialty within English departments, tasked with overseeing and evaluating a team of contingent faculty [13]. In addition, professors at large universities have increasingly conducted PTC seminars online over the past decade [11], and an exponential number will likely become virtual or hybrid instructors in the 2020-2021 school year due to safety concerns and gathering restrictions imposed in response to the COVID-19 outbreak.…”
Section: Instructor Training Opportunities and Pedagogical Challengesmentioning
confidence: 99%